Value transformation of modern Belarusian society (as results of sociological research) - Lashuk, Iryna V. (Journal of the Belarusian State University. Sociology, 2021)
The article presents the results of the study of the structure of the basic values of the Belarusian society using the method of constructing functional-oriented clusters of basic values by N. I. Lapin. The values that ensure the integration of the population of Belarus as a whole, as well as mediate the inclusion of the individual in the life-supporting, power-political and socio-cultural structures of society, were identified. The analysis of the degree of respondents’ support for basic values, grouped on additional grounds: according to their belonging to terminal (values-goals) or instrumental (values-means) values, and in accordance with cultural types of values (traditional, modern, universal values). It is revealed that the stable integrating core of the basic values of the Belarusian society are the values of human life and order. The recognition of the value and inviolability of human life occupies a dominant position in the hierarchy of basic values of Belarusians. The high level of support for the value of order indicates the great importance for the Belarusian society of stability and the organisation of social relations based on compliance with established laws and norms. However, the means of achievement have changed due to the increased importance of moral choice, which is expressed in the ability to help other people in need, even to the detriment of themselves, and the instrumental value of power, which is manifested in the desire to influence other people. A comparative analysis by year shows that in 2020 there was a serious increase in the importance of the universal group of values due to the decline in the demand for traditional and modern values. As in 2017, terminal values are more significant than instrumental values. Among the values-goals, the greatest support of the population in 2020 is human life, order and freedom; among the values-means – sacrifice and power. In order to study the variability of the value structure, a comparative study of the basic values of different age groups of the population was carried out. The intergenerational axiological analysis showed that in all age groups the integrating components are human life and order. At the same time, in the youth cohort, svoboda also entered the integrating core.
Keywords: basic values; terminal and instrumental values; sociocultural values; functional focusing clusters